Development of a Hamster Natural Transmission Model of SARS-CoV-2 Infection - Stuart Dowall; Francisco J. Salguero; Nathan Wiblin; Susan Fotheringham; Graham Hatch; Simon Parks; Kathryn Gowan; Debbie Harris; Oliver Carnell; Rachel Fell; Robert Watson; Victoria Graham; et al. (Viruses, 2021)
The global pandemic of coronavirus disease (COVID-19) caused by infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has led to an international thrust to study pathogenesis and evaluate interventions. Experimental infection of hamsters and the resulting respiratory disease is one of the preferred animal models since clinical signs of disease and virus shedding are similar to more severe cases of human COVID-19. The main route of challenge has been direct inoculation of the virus via the intranasal route. To resemble the natural infection, we designed a bespoke natural transmission cage system to assess whether recipient animals housed in physically separate adjacent cages could become infected from a challenged donor animal in a central cage, with equal airflow across the two side cages. To optimise viral shedding in the donor animals, a low and moderate challenge dose were compared after direct intranasal challenge, but similar viral shedding responses were observed and no discernible difference in kinetics. The results from our natural transmission set-up demonstrate that most recipient hamsters are infected within the system developed, with variation in the kinetics and levels of disease between individual animals. Common clinical outputs used for the assessment in directly-challenged hamsters, such as weight loss, are less obvious in hamsters who become infected from naturally acquiring the infection. The results demonstrate the utility of a natural transmission model for further work on assessing the differences between virus strains and evaluating interventions using a challenge system which more closely resembles human infection.